2020
DOI: 10.21577/0103-5053.20200025
|View full text |Cite
|
Sign up to set email alerts
|

High Conversion of Palm Olein to Ethyl Esters Using a Strong Anion Exchange Resin: Study of the Operational Parameters

Abstract: Biodiesel, known as a mixture of fatty acid ethyl/methyl esters, is seen as an alternative, ecofriendly, biodegradable and renewable non-fossil fuel. The use of heterogeneous catalysts for biodiesel synthesis can solve several problems associated with the homogeneous alkaline catalyzedtransesterification. Therefore, this work reports the evaluation of the commercial resin Amberlyst A26OH, a strong anion exchange resin, as a heterogeneous catalyst for the batch transesterification of refined palm olein with eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The ethanol concentration was also much higher than that used in the homogeneous catalysis. The high amount of ethanol that was required in the present study is in agreement with that reported in the literature for heterogeneous transesterification using an anion exchange resin; 4,11,21 both homogeneous and heterogeneous transesterifications stoichiometrically require 3 mol of alcohol for 1 mol of triacylglycerol, but, in practice, heterogeneous transesterification always uses a higher proportion. 31 In heterogeneous transesterification using a catalyst with a porous structure, the mass transfer resistance affects the external (between the reaction mixture and bulk solid phase) and internal (within the resin pores) movements of the chemical species.…”
Section: Kinetic Model Application: Comparison Between the Two Approa...supporting
confidence: 90%
See 4 more Smart Citations
“…The ethanol concentration was also much higher than that used in the homogeneous catalysis. The high amount of ethanol that was required in the present study is in agreement with that reported in the literature for heterogeneous transesterification using an anion exchange resin; 4,11,21 both homogeneous and heterogeneous transesterifications stoichiometrically require 3 mol of alcohol for 1 mol of triacylglycerol, but, in practice, heterogeneous transesterification always uses a higher proportion. 31 In heterogeneous transesterification using a catalyst with a porous structure, the mass transfer resistance affects the external (between the reaction mixture and bulk solid phase) and internal (within the resin pores) movements of the chemical species.…”
Section: Kinetic Model Application: Comparison Between the Two Approa...supporting
confidence: 90%
“…The ethanol concentration decreased with time, the rate of which was consistent with the production of FAEE. However, ethanol was the component that was present in the highest concentration in all studied cases at all times; this occurred because an excess of ethanol (ethanol/olein = 13:1) was used, as suggested by Bejarano-Alva et al 4 3.4. Adjustment of Kinetic Parameters for the Second Approach.…”
Section: Kinetic Model Application: Comparison Between the Two Approa...mentioning
confidence: 84%
See 3 more Smart Citations